Social Movements and Resistance: Extinction Rebellion Against Dominant Structures - Eltiby, Samira M. (AUC Knowledge Fountain, 2024)
Public dissent is the outcome of governments inaction regarding issues that populations deem as necessary. Social movements are groups that emerge due to dissatisfaction with the status quo that is presented by the current neoliberal world order. The new social movement that is studied in this thesis seeks emancipation, freedom, environmental justice and action, and the dismantlement of neoliberal capitalism as a system of production. This thesis examines the relevance of Gramscian analysis to the study of new social movements, with a focus on Gramscian hegemony and leaderless movements. The thesis uses Extinction Rebellion (XR), a UK-based movement that adopts nonviolent civil disobedience as its main case study to explore what can be uncovered through using Gramsci’s ideas when studying new social movements. The thesis concludes that Gramsci offers a useful lens to explore new social movements in a different angle than is done using other theories. The thesis's main contribution to existing literature is its focus on areas of weakness and potential reasons for failure of movements fighting the current hegemonic order and how they could be perceived as tools of the neoliberal world order that they fight using Gramsci’s theory.